New group chain acceptance sampling plans (NGChSP-1) using minimum angle method for generalized exponential distribution - Mohd Azri Pawan Teh; Nazrina Aziz; Zakiyah Zain (Penerbit Universiti Kebangsaan Malaysia, 2021)
The established group chain acceptance sampling plans (GChSP-1) functions with five acceptance criteria, while the modified group of chain acceptance sampling plans (MGChSP-1) operates with three acceptance criteria. Since the acceptance criteria affect the performances of the sampling plans, therefore, this article suggests a balanced approach by introducing a new group of chain acceptance sampling plans (NGChSP-1), where it functions with four acceptance criteria. The NGChSP-1 is developed by using minimum angle method which caters for producer’s and consumer’s risks. The generalized exponential distribution is selected as the lifetime distribution and the simulation for the NGChSP-1 is conducted at various values of design parameters using the Scilab programming. The finding shows that the optimal number of groups and the corresponding smallest theta for NGChSP-1 are smaller compared to those for the GChSP-1. For illustration purposes, the NGChSP-1 is then applied to real data of air conditioning equipment.